Chiari I Malformation as a Human Disease Model of Cerebellar Cognitive–Affective Dysfunction - William Davalan; William E. Butler; Jeremy D. Schmahmann; William Muñoz; Neel H. Mehta; Angelique C. Paulk; Kristopher T. Kahle (The Cerebellum, 2026)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Evaluating the sensitivity of a chronic plant bioassay relative to an independently derived predicted no-effect thresholds to support risk assessment of very hydrophobic organic chemicals - Aaron D. Redman; Miriam Leon Paumen; Daniel J. Letinski; Barbara A. Kelley; Cary Sutherland; Bryan M. Hedgpeth; Josh D. Butler; Roger Prince; Gail E. Bragin; Abraham J. Smith (Archives of Environmental Contamination and Toxicology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Colony life history of the tropical arboreal ant, Cephalotes goniodontus De Andrade, 1999 - I. A. E. Butler; T. Butterfield; M. Janda; D. M. Gordon (Insectes Sociaux, 2024)
Arboreal ants are ecologically important in tropical forests, but there are few studies using DNA markers to examine their population and colony structure. Colonies of the arboreal turtle ant Cephalotes goniodontus create trail networks through the canopy of the tropical forest, in dense vegetation where it is difficult to determine how long a nest is used and how neighboring colonies partition space. We monitored 53 nest sites for up to six years and, using seven microsatellite markers, genotyped samples of workers collected at or near 41 nests over 1–4 years. We calculated average relatedness within samples collected at a given location, and between samples collected at the same location in successive years, and performed pedigree analysis to predict the number of queens that produced each sample of workers. Fifteen samples were highly related ( r ≥ 0.6) from single colonies, of which 11 were monogynous and the remaining four had two queens; 19 were of intermediate relatedness (0.1 ≤ r < 0.6) with 1–6 queens, and 7 were groups of unrelated workers (r < 0.1) from at least 4 queens. Colonies persisted at the same nest site for 2–6 years. The smallest distance we found separating nests of different colonies was 16.2 m. It appears that different colonies may share foraging trails. Our study demonstrates the feasibility of using a cost-efficient genotyping method to provide information on colony structure and life history of ant species.

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Stage‐dependent effects of river flow and temperature regimes on the growth dynamics of an apex predator - Rick J. Stoffels; Kyle E. Weatherman; Nick R. Bond; John R. Morrongiello; Jason D. Thiem; Gavin Butler; Wayne Koster; R. Keller Kopf; Nicole McCasker; Qifeng Ye; Brenton Zampatti; Ben Broadhurst (Global Change Biology, 2020)
In the world's rivers, alteration of flow is a major driver of biodiversity decline. Global warming is now affecting the thermal and hydrological regimes of rivers, compounding the threat and complicating conservation planning. To inform management under a non‐stationary climate, we must improve our understanding of how flow and thermal regimes interact to affect the population dynamics of riverine biota. We used long‐term growth biochronologies, spanning 34 years and 400,000 km 2 , to model the growth dynamics of a long‐lived, apex predator (Murray cod) as a function of factors extrinsic (river discharge; air temperature; sub‐catchment) and intrinsic (age; individual) to the population. Annual growth of Murray cod showed significant, curvilinear, life‐stage‐specific responses to an interaction between annual discharge and temperature. Growth of early juveniles (age 1+ and 2+ years) exhibited a unimodal relationship with annual discharge, peaking near median annual discharge. Growth of late juveniles (3+ to 5+) and adults (>5+) increased with annual discharge, with the rate of increase being particularly high in adults, whose growth peaked during years with flooding. Years with very low annual discharge, as experienced during drought and under high abstraction, suppress growth rates of all Murray cod life‐stages. Unimodal relationships between growth and annual temperature were evident across all life stages. Contrary to expectations of the Temperature Size Rule, the annual air temperature at which maximum growth occurred increased with age. The stage‐specific response of Murray cod to annual discharge indicates that no single magnitude of annual discharge is optimal for cod populations, adding further weight to the case for maintaining and/or restoring flow variability in riverine ecosystems. With respect to climate change impacts, on balance our results indicate that the primary mechanism by which climate change threatens Murray cod growth is through alteration of river flows, not through warming annual mean temperatures per se.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

When rare species are not important: linking plot-based vegetation classifications and landscape-scale mapping in Australian savanna vegetation - E. Addicott; S. Laurance; M. Lyons; D. Butler; J. Neldner (Community Ecology, 2018)

Lack of alarm calls in a gregarious bird: models and videos of predators prompt alarm responses but no alarm calls by zebra finches - Nicole E. Butler; Robert D. Magrath; Richard A. Peters (Behavioral Ecology and Sociobiology, 2017)

Productivity dominated by picoplankton in a macro‐tidal tropical estuary, Darwin Harbour - D. Purcell‐Meyerink; J. Fortune; E. C. V. Butler (New Zealand Journal of Botany, 2017)
Productivity around the tropical coast of North Australia has been considered to be dominated by phytoplankton. The phytoplankton encompasses a large taxon which, dependent on the source definition, can vary significantly. Traditionally, they would only include pelagic photosynthetic organisms (autotrophic), yet more recently the definition is being revised to include heterotrophic organisms. Recent advancements in oceanography over the past three decades have found the prevalence in the global ocean of cyanobacteria of sizes ranging from 0.5–1.5 µm. Two cyanobacterial genera Synechoccocus and Prochlorococcus are now recognised to dominate phytoplankton cell counts and biomass specifically in the oligotrophic tropical and subtropical oceans. This study is the first to identify the importance of picoplankton as a foremost contributor to productivity in a macro‐tidal ecosystem in Northern Tropical Australia. Picoplankton was found to be the dominant group of primary producers (> 99% or 6 × 10 9 cells/L) within the phytoplankton in Darwin Harbour during the dry season of 2013. The larger phytoplankton > 2 µm contributed ( 2 cells/L) of the population. This study further defines the influences on this dynamic system that would allow the picoplankton community to thrive, highlighting the complexity of this nitrogen‐limited system, where nutrient cycling, including nitrogen fixation mediated possibly through the microbial community, plays a pertinent role. Other environmental influences include spring tides, spatial variation and increased turbidity which benefits heterotrophy over autotrophy in this ecosystem.

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Using a model based fourth-corner analysis to explain vegetation change following an extraordinary fire disturbance - S. E. Venn; C. M. Pickering; S. A. Butler; A. D. Letten (Oecologia, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Mechanism for proliferation inhibition by various selenium compounds and selenium-enriched broccoli extract in rat glial cells - Jan-Ying Yeh; Bor-Rung Ou; Yu-Chuan Liang; Joel Burchfiel; Judy A. Butler; Neil E. Forsberg; Philip D. Whanger (BioMetals, 2006)

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)

Cooperation during prey digestion between workers and larvae in the ant, Pheidole spadonia - D. L. Cassill; J. Butler; S. B. Vinson; D. E. Wheeler (Insectes Sociaux, 2005)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Thermoregulation during swimming and diving in bottlenose dolphins, Tursiops truncatus - D. P. Noren; T. M. Williams; P. Berry; E. Butler (Journal of Comparative Physiology B, 1999)

Corpuscles of Stannius and stanniocalcin-like immunoreactivity in the white sucker ( Catostomus commersoni ): evidence for a new cell-type - D. H. Zhang; G. Y. Oudit; L. E. Marra; D. G. Butler; J. H. Youson (Cell and Tissue Research, 1998)

Methyl parathion persistence in soil following simulated spillage - L. C. Butler; D. C. Staiff; J. E. Davis (Archives of Environmental Contamination and Toxicology, 1981)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)